2010
DOI: 10.1021/bi100660r
|View full text |Cite
|
Sign up to set email alerts
|

Binding Characteristics of Small Molecules That Mimic Nucleocapsid Protein-Induced Maturation of Stem-Loop 1 of HIV-1 RNA

Abstract: As a retrovirus, the human immunodeficiency virus (HIV-1) packages two copies of the RNA genome as a dimer in the infectious virion. Dimerization is initiated at the dimer initiation site (DIS) which encompasses stem-loop 1 (SL1) in the 5’-UTR of the genome. Study of genomic dimerization has been facilitated by the discovery that short RNA fragments containing SL1 can dimerize spontaneously without any protein factors. Based on the palindromic nature of SL1, a kissing loop model has been proposed. First, a met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…In their pursuit to identify compounds that bind to SL1 and inhibit SL1-NC interaction, Chung and colleagues have identified a peptide-based coumarin derivative compound, 19 (Fig 5), that binds the SL1 stem-bulge region, which appears to mimic the chaperoning effect of NC for SL1 (Chung et al, 2010). Although the identified compound is much less efficient at chaperoning than NC, the unique compounds and identification strategy opens a new avenue for identifying compounds that compete for NC and bind viral RNA.…”
Section: Rna Bindersmentioning
confidence: 99%
“…In their pursuit to identify compounds that bind to SL1 and inhibit SL1-NC interaction, Chung and colleagues have identified a peptide-based coumarin derivative compound, 19 (Fig 5), that binds the SL1 stem-bulge region, which appears to mimic the chaperoning effect of NC for SL1 (Chung et al, 2010). Although the identified compound is much less efficient at chaperoning than NC, the unique compounds and identification strategy opens a new avenue for identifying compounds that compete for NC and bind viral RNA.…”
Section: Rna Bindersmentioning
confidence: 99%
“…In addition to small molecule inhibitors, 1 H NMR analysis showed that polypeptides rich in tryptophan also interact with the GGAG tetraloop of the Ψ-hairpin, and possibly block NC binding [ 390 ]. The DIS region might also be targeted, since dimerization is a prerequisite for retroviral genome packaging [ 391 ].…”
Section: Inhibition Of Genome Packagingmentioning
confidence: 99%
“…The first stem-loop structure of the packaging site, SL1 forms the so-called kissing dimer, which is recognized by NCp7 and converted into a more stable extended duplex in the early stages of viral maturation. Using a virtual-screening-based procedure, James and colleagues compiled a list of potential kissing dimer binders [51,52] and, with a consecutive experimental screen based on a gel shift assay, they found that the coumarin derivative 28 (Fig. 4), instead of inhibiting, activated the conversion of the kissing dimer into the extended structure, thus unexpectedly acting as a NCp7 mimic.…”
Section: Sl Bindersmentioning
confidence: 99%
“…4), instead of inhibiting, activated the conversion of the kissing dimer into the extended structure, thus unexpectedly acting as a NCp7 mimic. Compound 28 might serve as a small-molecule tool to study NCp7-mediated maturation or as the starting point for the development of antivirals that activate viral maturation prematurely [52].…”
Section: Sl Bindersmentioning
confidence: 99%